CERTAIN ASPECTS OF ETHNICITY OF THE KAZAKHS OF CHINA - RAKISHEVA, Botagoz (CENTRAL ASIA AND THE CAUCASUS, 2015)
There are about 5 million Kazakhs living all over the world outside the Republic of Kazakhstan, the largest part of them predictably found in the Xinjiang Uyghur Autonomous Region of the PRC bordering on Kazakhstan.There are two distinct groups of Chinese Kazakhs: the clans that migrated to China to avoid collectivization in the Soviet Union and the larger one of indigenous Kazakhs.Today, the Kazakh diaspora, as all other diasporas for that matter, is facing the challenge of preserving its ethnic identity.The author analyzes the main results of the sociological studies of the life of the Kazakhs she has been carrying out since 2010 by different means: polls, in-depth interviews, and observations and polls of experts.The article contains certain results of sociological expeditions that studied four basic identities—linguistic, religious, zhuzclan, and cultural.This combination of different methods helps to analyze the social processes going on in the Kazakh diaspora, identify the impact of individual factors and the degree to which the ethnicity has been preserved, as well as the current state of ethnic identities, and forecast further development.